Electrically stimulated gene expression under exogenously applied electric fields - Abasi, Sara; Jain, Abhishek; Cooke, John P.; Guiseppi-Elie, Anthony (Frontiers in Molecular Biosciences, 2023)
Electrical stimulation, the application of an electric field to cells and tissues grown in culture to accelerate growth and tight junction formation among endothelial cells, could be impactful in cardiovascular tissue engineering, allotransplantation, and wound healing. Using Electrical Cell Stimulation And Recording Apparatus (ECSARA), the exploration of the stimulatory influences of electric fields of different magnitude and frequencies on growth and proliferation, trans endothelial electrical resistance (TEER) and gene expression of human endothelia cells (HUVECs) were explored. Within the range of endogenous electrical pulses studied, frequency was found to be more significant (p=0.05) than voltage in influencing HUVEC gene expression. Localization of Yes Associated Protein (YAP) and expression of CD-144 are shown to be consistent with temporal manifestations of TEER. This work introduces the field of electromics, the study of cellular gene expression profiles and their implications under the influence of exogenously applied electric fields. Homology of electrobiology and mechanobiology suggests use of such exogenous cues in tissue and regenerative engineering.